The European VLF/LF radio network to search for earthquake precursors: setting up and natural/man-made disturbances - Biagi, P.F. (2012)
In the last years disturbances in VLF/LF radio signals related to seismic activity have been presented. The radio data were collected by receivers located on the ground or on satellites. The ground-based research implies systematic data collection by a network of receivers. Since 2000 the “Pacific VLF network”, conducted by Japanese researchers, has been in operation. During 2008 a radio receiver was developed by the Italian factory Elettronika (Palo del Colle, Bari). The receiver is equipment working in VLF and LF bands. It can monitor 10 frequencies distributed in these bands and, for each of them, it saves the power level. At the beginning of 2009, five receivers were made for the realization of the “European VLF/LF Network”; two were planned for Italy and one for Greece, Turkey and Romania, respectively. In 2010 the network was enlarged to include a new receiver installed in Portugal. In this work, first the receiver and its setting up in the different places are described. Then, several disturbances in the radio signals related to the transmitters, receivers, meteorological/geomagnetic conditions are presented and described.